Students’ Perceptions of Native and Non-Native English-Speaking Teachers and Their Implications for English Language Learning - Afifa Zahara Sugandi; Marsha Fathia Jasmine; Aidil Syah Putra (Lembaga Pengembangan Kinerja Dosen, 2026)
English has increasingly functioned as global communication among people around the world with diverse cultural background. In this era, English is more frequently used among non-native speakers than native speakers themselves especially in academic, professional, and intercultural settings. Despite these developments, native speaker norms continue to have a strong influence in English language teaching and English language learning. NESTs are often viewed as a role model, and NNESTs viewed as someone who are incompetence in teaching a language. This research aims to find the strengths and weakness from students’ perspective, using a qualitative method and interview questions about each strength and weakness and their implication in English language learning. The result of this research was that each side was beneficial for students, as the NESTs helps with their pronunciation, idiomatic, and real-life communication usage to train students and building their confidence, and The NNESTs understood the students’ difficulties in learning and could be apply a teaching strategy to help them understand. However, the status of native or not wasn’t the important thing, it is the quality of teaching and the outcome for students so it will help them ready to communicate with people around the world.